2003
DOI: 10.1034/j.1600-0412.2003.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Long CAG repeats in theARgene are not associated with infertility in Finnish males

Abstract: At least in the present study population from Finland, long CAG repeats in the androgen receptor gene do not play a significant role in spermatogenic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
(37 reference statements)
3
25
1
Order By: Relevance
“…These results were consistent with other studies in which no association was found (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;Martinez-Garza et al, 2008;Badran et al, 2009), but discordant with other studies that did find associations (Tut et al, 1997;Komori et al, 1999;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). However, for CAG repeats >23, risks of >1.2-fold and >1.8-fold were found in azoospermia and severe oligospermia compared to the controls, although CAG repeat length was not significantly correlated with sperm counts in azoospermia and severe oligospermia.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results were consistent with other studies in which no association was found (Dadze et al, 2000;Sasagawa et al, 2001;Van Golde et al, 2002;Rajpert-De Meyts et al, 2002;Lund et al, 2003;Martinez-Garza et al, 2008;Badran et al, 2009), but discordant with other studies that did find associations (Tut et al, 1997;Komori et al, 1999;Dowsing et al, 1999;Yoshida et al, 1999;Mifsud et al, 2001;Patrizio et al, 2001;Wallerand et al, 2001;Mengual et al, 2003;Katagiri et al, 2006). However, for CAG repeats >23, risks of >1.2-fold and >1.8-fold were found in azoospermia and severe oligospermia compared to the controls, although CAG repeat length was not significantly correlated with sperm counts in azoospermia and severe oligospermia.…”
Section: Discussionsupporting
confidence: 83%
“…Several epidemiological studies have suggested a significant, albeit modest, impact of the repeat on clinical androgenic effects, with the GGN repeat being associated with the risk of prostate cancer (Hakimi et al, 1997), alopecia (Hillmer et al, 2005), hypospadias (Aschim et al, 2004), and breast cancer (González et al, 2007). Previous studies have reported inconsistent results on GGN lengths in fertile men (Tut et al, 1997;Lund et al, 2003;Ferlin et al, 2004;Ruhaye et al, 2004;Castro-Nallar et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding was then corroborated by several studies from a variety of different ethnic populations including Japanese, Caucasian, North American, French, Israeli, Taiwanese and Spanish (Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Wallerand et al 2001;Patrizio et al 2001;Madgar et al 2002;Pan et al 2002;Casella et al 2003;Asatiani et al 2003;Mengual et al 2003). However, several others, who have investigated Swedish, Belgian, German, Japanese, Danish, Dutch, Indian, Greek, New Zealander, Finish, Hong Kong Chinese and Italian populations were unable to demonstrate an association (Giwercman et al 1998;Legius et al 1999;Hiort et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Kukuvitis et al 2002;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Dhillon and Husain 2003;Erasmuson et al 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Interestingly, a study by Komori et al (1999) has suggested that reduction rather than expansion of the CAG repeat (< 16 repeats) is closely related to impaired sperm production in an infertile Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…decade (Tut et al 1997;Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Patrizio et al 2001;Wallerand et al 2001;Madgar et al 2002;Pan et al 2002;Asatiani et al 2003;Casella et al 2003;Mengual et al 2003), whereas several others were unable to demonstrate an association (Giwercman et al 1998;Hiort et al 1999;Legius et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Kukuvitis et al 2002;Erasmuson et al 2003;Dhillon and Husain 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Thus, the ethnic background of the population studied may play an important role in the correlation between CAG repeat length and male infertility.…”
mentioning
confidence: 99%